JOB DEMANDS AND WORK ENGAGEMENT: THE MEDIATING ROLE OF WORKPLACE WELL-BEING - Ratih Devi Aryanti; Erita Yuliasesti Diah Sari; Herlina Siwi Widiana (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
High work engagement can be supported by employees feeling happy and prosperous in the organization. Workplace well-being is important to have so that employees can exert their best performance to face all the demands in the work environment. Many studies have shown those job characteristics that are like job demands impact workers' well-being. This study aimed to determine whether there is an effect of job demands on work engagement with workplace well-being as a mediation. This study was conducted on 62 employees of X Publishers with a QRCP measuring instrument (21 items) to measure job demands, a workplace well-being scale (12 items) to measure workplace well-being, and a UWES measuring device (18 items) to measure work engagement. The data obtained were analyzed using the PROCESS by Hayes processed with SPSS for MacOS. The results indicated that job demands did not affect work engagement (p = 0.500). Workplace well-being was also proven not to mediate between job demands and work engagement (p = 0.508). Whereas workplace well-being has a very significant effect on work engagement (p = 0.000). Therefore workplace well-being is important to enhance work engagement of the employees